Analyze Locally & Act Locally”- Geographical Prioritization of Districts/Blocks & Strategic Approach Using HIV Data Triangulation in Gujarat, India - Chavan, Laxmikant; Pakhare, Abhijit; Gupta, Praveen; Choudhury, Lincoln (National Journal of Community Medicine, 2016)
Introduction: Apart from expanded surveillance data, National AIDS control Programme had generated lot of program data at district, state and national level. This rich data set can be used for priority action. In this study scoring triangulation methods used to assign priority among district by using programme data. Methods: Three different prioritization tools (scoring triangulation methods) were developed based on the routine programme and survey data. These three tools were used to give scoring to each district of the Gujarat state for assign priorities for programme implementation and expansion of services. Results: All 25 districts of the Gujarat state were categorised using the prioritization tools. As per the weighted seven indicator 12 districts are in high category while as per as Seven Indicators (Uniform) tool and Nine Indicators (Weighted) tool 7 and 5 district were in High category. Conclusion: This scoring triangulation method being a simple tool can be used at district, block level where diversity/multiplicity of HIV is unique. This method can be used to monitor geographical spread and impact of prevention activities in this area.